HDAC6 inhibition by ITF3756 modulates PD-L1 expression and monocyte phenotype: insights for a promising immune checkpoint blockade co-treatment therapy - Spadotto, Valeria; Ripamonti, Chiara; Ghiroldi, Andrea; Galbiati, Elisabetta; Pozzi, Pietro; Noberini, Roberta; Bonaldi, Tiziana; Steinkühler, Christian; Fossati, Gianluca (Frontiers in Immunology, 2025)
IntroductionTumor immunotherapy has revolutionized cancer treatment, particularly through the use of immune checkpoint inhibitors targeting the PD-L1/PD-1 axis. While PD-L1 expression on tumor cells is an established predictive biomarker for therapeutic response, emerging evidence highlights the importance of PD-L1 expression on myeloid cells, both in the periphery and within the tumor microenvironment (TME). This study explores the immunomodulatory effects of the selective HDAC6 inhibitor ITF3756 on monocytes and dendritic cells (DCs).MethodsMonocytes were stimulated with the pro-inflammatory cytokine TNF-α and treated with ITF3756. PD-L1 and CD40 expression levels were assessed by flow cytometry. Transcriptomic and proteomic analyses were performed to characterize changes in gene and protein expression profiles. T cell proliferation was evaluated in co-culture assays. Additionally, the impact of ITF3756 was assessed in an in vivo murine model of colon cancer.ResultsITF3756 effectively downregulated PD-L1 expression in TNF-α-activated monocytes and enhanced their costimulatory capacity by increasing CD40 expression. Transcriptomic and proteomic analyses revealed that ITF3756 counteracted TNF-α pathway activation and downregulated multiple inhibitory immune checkpoint molecules, promoting a less immunosuppressive phenotype. In co-culture assays, ITF3756-treated monocytes and DCs significantly enhanced T cell proliferation. In vivo, ITF3756 treatment led to reduced tumor growth in a colon cancer model.DiscussionThese findings demonstrate that selective HDAC6 inhibition by ITF3756 modulates myeloid cell functionality by diminishing inhibitory signals and promoting T cell activation. Thus, ITF3756 represents a promising immunomodulatory agent that could enhance the efficacy of immune checkpoint blockade in cancer immunotherapy.